Analysis of Water Demand in Student Dormitories: An Example of an Unconventional Residential Building - Dykiert, Karol; Cieżak, Wojciech (Instal, 2025)
Water demand analysis is a critical tool in the effective management of water supply networks, supporting a wide range of operational and strategic tasks. These include network planning, modernisation efforts, investment decisionmaking, flow and pressure optimisation, and determining appropriate connection parameters for newly designed buildings. Depending on the objective, such analyses can take various forms, ranging from fundamental statistical evaluations to more advanced studies that incorporate multiple factors influencing water demand. This study focuses on the development and characterisation of a water consumption pattern for a student dormitory in Wrocław. Given the unique nature of dormitory water usage, particular attention was paid to comparing water demand between working days and weekends. By employing a two-means statistical test, the analysis revealed that while the time series representing daily water consumption on weekdays and weekends exhibit distinct characteristics, the overall average daily water consumption remains statistically equivalent. These findings suggest that although students adjust their water usage habits based on their schedules the total volume of water consumed remains stable across different days of the week. Such insights are valuable for water supply network managers, enabling more precise demand forecasting and ensuring efficient system operation, particularly in areas with a high concentration of similar residential buildings.
Keywords: water consumption; water consumption pattern; water consumption analysis; water distribution system; water demand